Power, voice and the public good schooling and education in global societies - Hopson, Rodney K. (Rodney Kofi); Yeakey, Carol Camp; Boakari, Francis Musa (Advances in education in diverse communities ;, 2008)
Three themes underpin the tripartite structure of "Power, Voice, and the Public Good", including attention to the definitional and theoretical underpinnings of globalization; the ubiquitous nature and topical display of globalization; and, the possibilities of understanding, redefining and rethinking aspects of globalization with the backdrop of issues that relate to education, and the pursuit of public good. A plethora of examples how education and schooling respond to and are driven by larger global networks, demands, and discourses are explored. Each chapter of the book consistently addresses ways of looking at the hope and promise of education and schooling in spite of the advent, realities, and complexities of their globalized societies.